Efetividade e sensibilidade ao clareamento dental caseiro realizado com peróxido de hidrogênio 4% e 10%: estudo clínico randomizado triplo cego - Chemin, Kaprice (2016)
The aim of this study was to clinically evaluate the effectiveness, stability of color and dental sensitivity of at-home dental bleaching with 4% and 10% hydrogen peroxide (H2O2). For this study, 78 patients were selected according to the inclusion and exclusion criteria, with central maxillary incisors A2 or darker, compared to Vita Classical shade guide (Vita Zahnfabrik, Bad Säckingen, Germany), and they were randomized into two groups: G10% – 10% H2O2 (White Class with Calcium 10% - FGM, Joinville, SC, Brazil) and G4% – 4% H2O2 (White Class with Calcium 4% - FGM, Joinville, SC, Brazil). The bleaching was carried out with White Class with Calcium, FGM, Joinville, SC, Brazil) for a period of 30 minutes twice a day for two weeks for both concentrations. The color was assessed by Vita Classical (Vita Zahnfabrik, Bad Säckingen, Germany), Vita Bleachedguide 3D-MASTER (Vita Zahnfabrik) and spectrophotometer Vita Easyshade (Vita Zahnfabrik, Bad Säckingen, Germany) initially during bleaching (1st and 2nd weeks) and after this bleaching procedure (1 month). The tooth sensitivity was recorded by the patients, using a numeric rating scale (NRS, 0-4) and visual analogue scale (VAS, 0-10). We carried out the Mann-Whitney test for contrast of means (α=0.05). The tooth sensitivity was evaluated by Chi-square test and the intensity of tooth sensitivity was evaluated by Mann-Whitney test (α=0.05) for both scales. Data from ΔSGU and ΔE showed an effectiveness of dental bleaching in both groups after two weeks of treatment. The prevalence of tooth sensitivity was higher in the group that used 10% H2O2. It can be concluded that at-home bleaching is effective for both groups, and 4% H2O2 decreased the absolute risk intensity of tooth sensitivity in at-home dental bleaching.